2022
DOI: 10.4314/ajcem.v23i2.11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of vector-borne bacterial pathogens in dromedary camels from Algeria

Abstract: Background: In Algeria, little focus was placed on camels as hosts of tick-borne bacterial diseases. Recent studies showed a high prevalence of tick infestation in dromedaries. Transmission of various pathogenic micro organisms to camels by ticks imposes considerable economic losses to livestock and greatly impact on human and animal health. The aim of our study was to investigate the occurrence of vector-borne zoonotic bacteria in camels from Algeria. Methodology: Blood samples were collected from 80 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…in ruminants (8.5% goats, 6.6% sheep, 3.1% cattle) and dromedary (1.9%) from Somalia. Previous studies conducted in dromedaries from Tunisia and Algeria also reported lower prevalence rates of 3.6% % (Selmi et al., 2020) and 2.6% (Bessas et al., 2022), respectively. On the other hand, a prevalence of 17% was found in dromedaries from Iran (Ghaemi et al., 2019).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…in ruminants (8.5% goats, 6.6% sheep, 3.1% cattle) and dromedary (1.9%) from Somalia. Previous studies conducted in dromedaries from Tunisia and Algeria also reported lower prevalence rates of 3.6% % (Selmi et al., 2020) and 2.6% (Bessas et al., 2022), respectively. On the other hand, a prevalence of 17% was found in dromedaries from Iran (Ghaemi et al., 2019).…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, studies conducted in Iran (Bahari et al., 2021) and Palestine (Ereqat et al., 2016) recorded negative results among dromedaries. Herein, while B. henselae was detected in a dromedary, ‘ Candidatus B. dromedarii’ was documented in dromedary from Algeria (Bessas et al., 2022) and Iran (Ghaemi et al., 2019). B. henselae has already been detected in dromedary from Tunisia (Selmi et al., 2020).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(i.e., A. marginale, A. platys , and A. ovis ) were detected in apparently healthy camels. Anaplasma spp., including A. phagocytophilum , have previously been detected in camels from Saudi Arabi ( Alanazi et al., 2020 ), Algeria ( Bessas et al., 2022 ), and the United Arab Emirates ( El Tigani-Asil et al., 2021 ). Further, in Ben Said et al.…”
Section: Discussionmentioning
confidence: 99%